Knowledge, (mis-)conceptions, risk perception, and behavior change during pandemics: A scoping review of 149 studies. (November 2020) - Majid, Umair; Wasim, Aghna; Bakshi, Simran; Truong, Judy
The severe acute respiratory syndrome–coronavirus-2 pandemic has spread rapidly and has a growing impact on individuals, communities, and healthcare systems worldwide. At the core of any pandemic response is the ability of authorities and other stakeholders to react appropriately by promoting hygiene and social distancing behaviors. Successfully reaching this goal requires both individual and collective efforts to drastically modify daily routines and activities. There is a need to clarify how knowledge and awareness of disease influence risk perception, and subsequent behavior in the context of pandemics and global outbreaks. We conducted a scoping review of 149 studies spanning different regions and populations to examine the relationships between knowledge, risk perceptions, and behavior change. We analyzed studies on five major pandemics or outbreaks in the twenty-first century: severe acute respiratory syndrome, influenza A/H1N1, Middle East respiratory syndrome, Ebola virus disease, and coronavirus disease 2019.